The Diversity of Induced M1V4 Mutant Population of Cassava (Mahinot Esculanta Crantz) - Kinyua, Miriam; Okwaro, Henry (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2021)
Cassava owns a small genome (about 770 Mb), it is considered as an allopolyploid with a high level of heterozygosity characteristics which severely hamper the speed and ease of introgressing useful genes in cassava. Mutation techniques form a classical procedure of development of variation in crops like cassava while genetic markers can be used to reveal genetic variation in the germplasm. This study was undertaken to determine the genetic relatedness of mutagenised cassava early generation populations through phenotypic and genetic marker procedures. Diversity of mutagenised population of cassava at M1V4 generation was examined at seedling stage in the greenhouse and at adult stage in the field through checking phenotypic and genetic traits. Plant height, number of lobes on leaves, petiole colour, number of nodes per stem and gel separation of PCR products developed from SSR markers differed significantly between selected putative mutants as well as in comparison with parent line. For example plant height of the 10 selected mutants ranged from 16 cm to 113cm where the parent grew to 24.33 cm while the number of nodes ranged from 11 to 24 with the parent having 13 nodes. Diversity of the mutant lines was demonstrated and further studies can be undertaken to quantify the variation for breeding and production of cassava.